2016
DOI: 10.1136/postgradmedj-2015-133487
|View full text |Cite
|
Sign up to set email alerts
|

The impact of clinical maturity on competency in evidence-based medicine: a mixed-methods study

Abstract: Clinical maturity is the only one factor that may influence medical trainees' competency in EBM. Other predictors of EBM competency may include previous training and exposure to epidemiology, biostatistics and information literacy. While graduate-entry medical students may have more 'life' experience, or maturity, it does not necessarily translate into clinical maturity and integration into the clinical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Also, previous research experience appears to be associated with EBM skill mastery, as shown in the 19-point (98–79) higher average score between those who have and have not participated in research. Previous investigation of EBM found a 52-point average difference between novices and experts, 7 which suggests that these average differences, while not at the same magnitude, are meaningful. For example, the difference between a resident who has and has not had previous research experience is over a third of the difference between an EBM novice and expert.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, previous research experience appears to be associated with EBM skill mastery, as shown in the 19-point (98–79) higher average score between those who have and have not participated in research. Previous investigation of EBM found a 52-point average difference between novices and experts, 7 which suggests that these average differences, while not at the same magnitude, are meaningful. For example, the difference between a resident who has and has not had previous research experience is over a third of the difference between an EBM novice and expert.…”
Section: Resultsmentioning
confidence: 95%
“… 6 Additionally, previous studies showed limited success in helping residents develop these EBM skills and knowledge, especially in contrast to medical students. 7 , 8 Finally, most studies do not consider residents’ previous experience when assessing their changes in EBM capacities, and thus, we have limited understanding on which experiences matter more in terms of long-term EBM development. Thus, we aim to provide insight into what experiences are associated with residents’ development of EBM attitudes, habits, and skills.…”
Section: Introductionmentioning
confidence: 99%
“…pathophysiology and pharmacology courses) and also attend a mandatory course in evidence-based medicine (addressing concepts such as number needed to treat, risk reduction, odds ratio, meta-analysis), which may have contributed to the high numeracy levels observed at their entrance to the fourth study year. Previous research also indicated that clinical maturity is an important factor which may contribute to the improvement of critical reflection and numerical understanding in health context, which may also be a reason why students at clinical years had higher scores [22]. Moreover, at the clinical part of the medical curriculum, it is to be expected that students perform calculations in a clinical context daily, and thus keep their high numeracy levels.…”
Section: Discussionmentioning
confidence: 99%
“…A focus group was conducted six months into the academic year, to allow enough time for the interns to become familiar with all of the EBM curricular components. The focus group goal was to better explore residents’ subjective evaluation regarding the EBM curriculum and to explore their views on how the curriculum improved their ability to more confidently apply EBM skills 1618. Preparation and execution of the focus group was based on the checklist published by Tong et al18…”
Section: Methodsmentioning
confidence: 99%